The effect of wall strengtheners on the performance of double-stage electrostatic precipitators (Iranian Journal of Chemical Engineering)
The presence of wall strengtheners in double-stage electrostatic precipitators affects gas velocity, electrical field and particle movement over the ESP. In this work we have used our previous mathematical model for double-stage ESP {Talaie et. al (2001) [10]] to study the effect of wall strengtheners on the performance of double-stage ESP. One of the important findings was that, due to the fact that wall strengtheners increase the degree of turbulence, the effect of gas turbulence on particle movement can not be ignored. The results of the calculations show that the simple Lagrangian model in which this effect is neglected is not suitable, whereas using an Eulerian approach provides much better results. The results of this model also revealed that the collection efficiency for small particles increases while that for large particles decreases when a baffle is used as wall strengthener.